ADDRESSING CHALLENGES IN EARLY IDENTIFICATION AND INTERVENTION OF AUTISM SPECTRUM DISORDER - Silva , Lorena Rebouças da (2024)
Autism Spectrum Disorder (ASD) is considered a neurodevelopmental disorder characterized by deficient social interaction and communication, stereotyped and repetitive patterns of behavior and irregular intellectual development, often with mental retardation. This study reviewed the challenges associated with the early diagnosis and treatment of ASD, emphasizing the importance of early identification of characteristic signs and symptoms of the condition. Guidelines for the Rehabilitation of Individuals with ASD underscore the crucial need for early interventions to improve the clinical condition of affected individuals. However, the average age of diagnosis in Brazil still falls short of ideal, indicating an urgent need to promote early detection and reduce delays in accessing early intervention services. Challenges in the early diagnosis and treatment of ASD include variations in the clinical presentation of the condition, lack of standardized screening tools, and healthcare professionals' unfamiliarity with early signs of ASD. Despite these obstacles, early interventions are associated with significant gains in the cognitive and adaptive functioning of affected children. Therefore, it is essential to adopt integrated and collaborative approaches to address these challenges and improve ASD management.